Intratumoral Heterogeneity of Genomic Imbalance in a Case of Epithelioid Glioblastoma with BRAF V600E Mutation - Nobusawa, Sumihito (Brain Pathol, 2014)
Epithelioid glioblastoma is among the rarest variants of glioblastoma and is not formally recognized in the World Health Organization classification; it is composed of monotonous, discohesive sheets of small, round cells with eccentric nuclei and eosinophilic cytoplasm devoid of cytoplasmic stellate processes, showing the retention of nuclear staining of INI‐1 protein. Here, we report a case involving a 22‐year‐old man with a right occipital lobe tumor, which comprised mainly epithelioid tumor cells with a small area of diffusely infiltrating less atypical astrocytoma cells showing a lower cell density. Array comparative genomic hybridization separately performed for each histologically distinct component demonstrated eight shared copy number alterations (CNAs) and three CNAs observed only in epithelioid cells; one of the latter was a homozygous deletion of a tumor suppressor gene, LSAMP, at 3q13.31. BRAF V600E mutation was observed both in epithelioid tumor cells and in diffusely infiltrating less atypical astrocytoma cells. Our findings suggest that the regional loss of LSAMP led to the aggressive nature of epithelioid cells in the present case of epithelioid glioblastoma.